RANCANG BANGUN CHASIS PIN HOLDER PADA TRIBOMETER PIN ON DISC BERBASIS MODIFIKASI PADA MESIN BUBUT KONVENSIONAL - Daris Miftah Dzaky; Abdul Aziz; Imam Saefulloh; Sidik Susilo; Indah Uswatun Hasanah (UNIVERSITAS SRIWIJAYA, 2021)
Tribometer is an instrument that measures the amount of tribological, coefficient of friction, frictional strength, volume of wear and lubrication between two contact surfaces in tribology studies. Tribotester Pin On Disc is a friction and wear test tool consisting of a pin and a disc. Pins have various shapes and sizes, generally spherical or cylindrical in shape, while discs with a certain thickness are in the form of diameter plates. Utilization of conventional lathes to be used as pin on disc tribometers requires modification and adding other components. This study uses the Library Research method to collect data. Designing a pin on disc tribometer based on a conventional lathe is done by designing a tool and then making a pin holder frame that utilizes part of a conventional lathe, namely the sled rail. This study also tested the pin material and disk material as test materials to determine the wear of the material tested using a conventional lathe-based Pin On Disc by obtaining the data results obtained from the pin on disk testing of aluminum material without lubrication. The largest wear factor value is at a distance of 1.2528 km. that is equal to 0.0127 mm3/NmKeywords: tribology, tribometer, pin on disc